The Conflict of European and Eastern Algonkian Cultures, 1504-1700 : A Study in Canadian Civilization, Second Edition - Bailey, Alfred Goldsworthy (Book collections on Project MUSE., 1969)
This study examines the conflict between the Europeans and the Indians precipitated by the arrival of the French in the New World.